Ethnobotanical study of Zapotitlan Salina, Puebla - Paredes-Flores, Martín; Lira Saade, Rafael; Dávila Aranda, Patricia D. (Instituto de Ecología, A.C., 2007)
In this paper, we document the role and potential of plant resources in the Popoloca community of Zapotitlán Salinas, Puebla, located in the most arid zone of the Tehuacán-Cuicatlán Valley. In total, 298 species belonging to 82 families were found. Ethnobotanical information is included for 288 species belonging to 219 genera and 79 botanical families, whose uses are placed in 19 categories. A total of 164 species are wild plants growing in different natural plant communities and in some of the transformed areas, while 124 can be found exclusively in the homegardens. The families with the highest number of useful plants were Poaceae (35 spp.), Cactaceae (24 spp.), and Asteraceae (23 spp.). Most of the useful plants are herbs (162 spp.), followed by shrubs (86 spp.) and trees (41 spp.). The paper includes information about spatial and seasonal availability of the useful species, as well as data concerning relative importance of the most important ones, such as those used as medicine, food, firewood and fodder.